Pentecostal and Charismatic Christianity in South Africa and Zimbabwe: A Review - Ganiel, Gladys (Religion compass, 2010)
Pentecostal/charismatic Christianity is the fastest-growing religion in southern Africa. This article explores its social and political roles, drawing primarily on examples from South Africa and Zimbabwe to illuminate wider trends across the continent. It considers the main competing assessments of Pentecostal/charismatic Christianity in Africa: (1) it is dominated by the ‘prosperity gospel’ and therefore stunts real economic growth and development; (2) it is primarily an apolitical faith that distracts people from their suffering; and (3) it is a Western import that disables the development of African cultures. It concludes that Pentecostal/charismatic Christianity in South Africa and Zimbabwe has included all of these elements. But recent research indicates that Pentecostal/charismatic Christianity is increasingly a socially and politically active religion that is surprisingly well-placed to meet people’s economic and material needs, to empower people to participate in civic and public life, and to promote reconciliation between previously opposing groups.